Proposição de framework para a análise da ilusão fiscal, seus antecedentes e consequentes - Silva, Jandeson Dantas da (Universidade do Vale do Rio dos Sinos, 2023)
The general objective of this research is to propose a framework to analyze the fiscal illusion, its antecedents and consequences in the perception of Brazilian taxpayers. The study fits in as to the methodological typology as descriptive, using the survey as a procedure and the approach of the quantitative problem, resorting to the Structural Equation Modeling technique - SEM. The research instrument was characterized by a controlled one, which was answered by 618 Brazilian contributors. An instrument was developed to measure the antecedent and consequent elements of the fiscal illusion, through a theoretical survey and validated through the factorial analysis technique. After adjusting the model, the results show that there is meaning between the construction of the fiscal illusion and its antecedents: open data, budgetary governance, fiscal governance. The analysis involving the fiscal illusion and citizen participation points to the existence of a significant relationship. In addition, the proposed integrated model indicates the possibility of improvement in the adjustment indices from the consideration of correlations raised between the constructs: open data and budgetary governance, open data and fiscal governance, budgetary governance, and fiscal governance. In this way, it is concluded that the behavior of the fiscal illusion is influenced by, and simultaneously influences, the performance of the antecedents open data, fiscal governance and budgetary governance, as well as the illusion influences the conduct of the citizen participation construct. In addition, it was identified that the performance of the antecedents influences and is influenced by the way in which the other antecedent constructs work, as they correlate with each other. The proposed framework, validated, to analyze the fiscal illusion, its antecedents and consequences constitutes a contribution to science, addressing theoretical gaps, in addition to collaborating with society and with the functioning of public administration. Despite the proposed model contemplating academic, social and management needs, other constructs can be included, as well as other publics can be investigated.
Keywords: Ilusão fiscal; Contribuintes; Participação cidadã; Governança; MEE; Fiscal illusion; Taxpayers; Citizen participation; Governance; SEM; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis